MODERN APPROACHES TO INFECTION PREVENTION AFTER UTERINE ARTERY EMBOLIZATION IN UTERINE MYOMA - Ющенко, Марина Анатольевна; Мозес, Вадим Гельевич; Рудаева, Елена Владимировна; Елгина, Светлана Ивановна; Мозес, Кира Борисовна; Рыбников, Сергей Валерьевич; Центер, Яэль (Mother and Baby in Kuzbass, 2023)
Information was searched for PubMed, Scopus, Webof-science, RSCI databases using the following keywords: infection prevention, uterine artery embolization, uterine myoma, etiology, pathogenesis, diagnosis, treatment, without language restrictions. For the analysis, 34 sources with full access to the text were selected, 50 % of which were published within the last five years, and 90 % within the last three years. The criteria for excluding sources were low information content and outdated data. Uterine artery embolization (UAE) is an effective and safe procedure with a low overall incidence of postoperative uterine infections (< 2.5 %), similar to myomectomy. The entrance gate of infection in UAE is most likely a procedural arterial access or cervical canal for vaginal microflora. For the prevention of postoperative infectious complications, intravenous antibiotics are recommended within an hour before the incision on the skin. It should be noted that many of the conclusions and recommendations regarding approaches to infection prevention after uterine artery embolization for uterine fibroids are based on low-quality studies with insufficient follow-up. In the strategy of combating infectious complications in UAE, further large randomized clinical trials are needed to create unified approaches based on evidence-based medicine.